The Principle of People's Sovereignty in the Presidential Appointment of the Head of the Nusantara Capital Authority - Elvia Rahmawati; Miftakhul Huda; Ian Firstian Aldhi (Journal of Law, Politic and Humanities, 2024)
This study explores the appointment mechanism of the Head of the Nusantara Capital Authority (IKN Authority) and its implications for the principle of people's sovereignty as enshrined in the 1945 Constitution. The Indonesian state, structured as a unitary system with decentralized governance, grants certain regions special status, including the newly established Nusantara Capital. Unlike other regions with locally elected leaders, the Head of the IKN Authority is appointed directly by the President, reflecting an asymmetric decentralization model. The findings indicate that while the special appointment mechanism aims to streamline governance and ensure efficient leadership for the capital's development, it significantly limits local political representation and public participation. The study highlights that this mechanism contrasts with democratic principles outlined in the Constitution, where sovereignty is vested in the people and manifested through elections. The reliance on a merit-based appointment system underscores the need for professional leadership in managing the complex and multi-sectoral environment of the new capital. However, it also raises concerns about the diminishing role of public consent and local political engagement, which are vital to democratic governance. The study concludes that while the mechanism facilitates the capital's development, it simultaneously weakens democratic values by curbing the practical exercise of people's sovereignty at the local level.